Posterior Cruciate Ligament Preservation versus Posterior Cruciate Ligament Sacrifice: Comparing Patient Outcomes in Medial Congruent Total Knee Arthroplasty - Guild, George N., III; McConnell, Mary J.; Najafi, Farideh; Naylor, Brandon H.; DeCook, Charles A.; Bradbury, Thomas L. (The Journal of Knee Surgery, 2024)
This study aimed to compare outcomes and complication rates between posterior cruciate ligament (PCL) retention and excision utilizing a medial congruent (MC) polyethylene insert in total knee arthroplasty (TKA) in a specialized ambulatory surgery center (ASC) dedicated to hip and knee arthroplasty. A retrospective review was performed between May 2023 and October 2023 analyzing 398 patients who underwent primary MC TKA by high-volume joint arthroplasty surgeons (n = 9) with either PCL preservation (n = 264) or sacrifice (n = 134) in a single free-standing ASC. Patients were matched chronologically on a 2:1 basis. Demographics, baseline function, 90-day complications, and patient-reported outcomes were recorded for each patient. There were no differences in preoperative baseline function or patient-reported outcome measures, Charlson Comorbidity Index, or American Society of Anesthesiologists class among patient groups. The PCL-preserve and PCL-sacrifice cohorts showed significant variation in 12-week postoperative Knee Injury and Osteoarthritis Outcome, Junior (KOOS, JR.) scores. Specifically, the number of patients who achieved the minimal clinically important difference (MCID) in KOOS, JR. scores was higher in the PCL-sacrifice group (p < 0.05). Yet, no complications within the 90-day period were associated with PCL status and other patient-reported outcomes. This study comparing outcomes between MC TKAs with PCL retention and sacrifice suggests that both techniques are viable options with similar functional outcomes, pain scores, and complication rates, which may have benefits in an ASC setting. The PCL-sacrifice group exhibited a statistically significant increase in patients who achieved the MCID in KOOS, JR. score compared with the PCL-preserving at early follow-up. Future research should employ prospective, randomized designs to further validate these findings and explore long-term implications.
Keywords: medial congruent polyethylene; posterior cruciate ligament; ambulatory surgery center; total knee arthroplasty